1967
DOI: 10.1002/pssb.19670200139
|View full text |Cite
|
Sign up to set email alerts
|

F‐Center Formation by Fundamental Absorption in KI

Abstract: Irradiation of KI in the fundamental edge results in a temperature dependent rate of F-center growth predominantly proportional to the inverse of the number of F-centers already produced. This is related to a new experimental resultthe quenching of low temperature luminescence in irradiatively colored crystals. In addition, the production of F-centers by absorption in perturbed exciton bands and the intrinsic production of u-centers are discussed.Bestrahlung von K J in der Bandkante fuhrt zu einer temperaturab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1971
1971
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Parker [5] reported on the excitoninduced F-center growth in KI and KBr crystals, where the F-center growth was found to be a volume process and the concentration was found to have a square-root dependence on the number of absorbed photons. Goldstein [6,7] also showed that in KI, the optical density at the F band peak goes like the square root of time of irradiation by deuterium UV light. Later, Kristianpoller and Israeli [8] and Israeli et al [9] explained the linear and non-linear dose dependencies of thermoluminescence (TL), previously reported in different materials by these excitonic processes.…”
Section: Introductionmentioning
confidence: 96%
“…Parker [5] reported on the excitoninduced F-center growth in KI and KBr crystals, where the F-center growth was found to be a volume process and the concentration was found to have a square-root dependence on the number of absorbed photons. Goldstein [6,7] also showed that in KI, the optical density at the F band peak goes like the square root of time of irradiation by deuterium UV light. Later, Kristianpoller and Israeli [8] and Israeli et al [9] explained the linear and non-linear dose dependencies of thermoluminescence (TL), previously reported in different materials by these excitonic processes.…”
Section: Introductionmentioning
confidence: 96%
“…L'extinction de la photoluminescence du cristal pur est mesurée de la même façon car la profondeur de pénétration des électrons est supérieure à celle de la lumière de photoexcitation UV (de l'ordre de la longueur d'onde). En créant les défauts par irradiation électronique, nous avons alors l'avantage, sur les expériences où les défauts sont formés par irradiation UV [5], d'obtenir une coloration uniforme dans toute la couche irradiée et de pouvoir ainsi effectuer une mesure précise de la concentration en défauts.…”
Section: Mesuresunclassified